La esmeralda: imaginarios de un paisaje piscinero (2020)
The visual imaginaries and aesthetic experiences produced by pools are characterized by a common attraction made up of the space, the objects and the actions that take place within the space of swimming pools. The analysis of these aquatic landscapes generates hints of different aesthetic dimensions that occur around these scenarios. Starting from the study of water as a hypnotic and regenerating element, the singularities of the objects around it, its aesthetic atmosphere, the feelings it evokes and its graphic and stereotyped image that alludes to a paradisiac state or site, it is proposed to design an imaginary brand that talks about the gráfica popular piscinera and the spatial dislocations of swimming pools aesthetics. From a course called La Esmeralda, it is intended to synthesize conceptual topics through typographical interventions on present and recurring objects around domesticated aquatic settings. Through photographic direction, objects such as towels, floats, bathing caps, sunbathing t-shirts and swimming pool typographic signs are contextualized enhancing a commercial aspect and humor, thus reflecting on the imaginaries of the swimming pool aesthetic.